Anallisisis Digital Literacy In Staf Hotelgrand In Slawi - Ratri Wikaningtyas; Wiyanti Wiyanti (International Forum of Researchers and Lecturers, 2025)
The study is titled Analysis of Digital Literacy Ability Levels at Grand Dian Slawi Hotel Staff. The purpose of the study is to evaluate and understand the level of digital literacy capabilities owned by Hotel Grand Dian Slawi staff in various aspects, such as the use of information technology, digital communication, online collaboration and data security. The study used a quantitative approach with survey methods using questionnaires deployed to 26 hotel staff. The results of the study showed that most staff have excellent digital literacy rates with an average percentage of 92.31%. There are still some aspects that need to be improved, such as understanding digital ethics and valid information selection. The findings provide useful insights for the development of training programs that are more effective in improving digital skills in hospitality work environments. Keywords digital literacy, hotel staff, information technology, digital communication